2017
DOI: 10.3390/ma10111320
|View full text |Cite
|
Sign up to set email alerts
|

Calcined Chitosan-Supported Layered Double Hydroxides: An Efficient and Recyclable Adsorbent for the Removal of Fluoride from an Aqueous Solution

Abstract: In this work, calcined chitosan-supported layered double hydroxides (CSLDO) were synthesized through a co-precipitation method that restrained the particles’ aggregation of LDHs and exhibited huge specific surface areas, which can enhance the fluoride adsorption capacity. CSLDOs were characterized by physical and chemical methods and used for fluoride adsorption in an aqueous solution. The results indicated that the nanoparticles were constructed first and then assembled to form a porous and layered structure,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…Besides, to prepare one kind of nacre-like material with excellent mechanical properties, the choice of inorganic layered materials congregated with CS is very important [20]. Supported by different technology, Chen et al [21] inserted different proportions of cationic biopolymer chitosan and quaternate hemicellulose in montmorillonite (MMT) to get compact and robust nanocomposite films with a nacre-like structure and multifunctional characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, to prepare one kind of nacre-like material with excellent mechanical properties, the choice of inorganic layered materials congregated with CS is very important [20]. Supported by different technology, Chen et al [21] inserted different proportions of cationic biopolymer chitosan and quaternate hemicellulose in montmorillonite (MMT) to get compact and robust nanocomposite films with a nacre-like structure and multifunctional characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…The existing chitosan in the beads, of both materials, maintains the protonated amino groups along the chain and this facilitates the electrostatic interaction between the polymer chains and the negative charge of the fluoride [20]. The adsorption capacity with the Ch-PVA-TPP material was not significant, concerning the other materials (Ch-PVA-5EGDE, Ch-PVA-7EGDE and Ch-PVA-NaOH-TPP), this could possibly be because the cross-linking material occupied the active sites of chitosan beads [19]. Likewise, it was observed that the hydrogel of Ch-PVA-NaOH-TPP showed greater absorption of fluoride at pH 5, followed by pH 7 and pH 6.…”
Section: Effect Of Ph On Fluoride Adsorptionmentioning
confidence: 99%
“…A convenient pore classification, was originally proposed by Dubinin in 1992 and, subsequently, officially adopted by the International Union of Pure and Applied Chemistry (IUPAC). This classification is based on the properties that the different pores have according to their dimension in the adsorption processes and are manifested in the adsorption isotherms, according to this consideration the analyzed material can be classified as mesoporous [19,37].…”
Section: Effect Of Ph On Fluoride Adsorptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Excessive fluoride in natural water is predominantly caused by the discharge of fluoride-rich wastewater effluent or surface water washing of fluoridecontaining ore over long periods [1,2]. Excessive fluoride in the human body can mineralize calcium hydroxyphosphate to calcium fluorophosphate, which causes a significant change in the fluoride-phosphorus ratio resulting in spurs, periosteal hyperplasia, osteoporosis, osteosclerosis, and bone deformation [3,4]. Long-term intake of high-fluoride food by children will result in enamel hypoplasia, tooth damage, and fluoride deposition, causing a series of deformities in the bones [5,6].…”
Section: Introductionmentioning
confidence: 99%